MODAL SOSIAL PELAKU DALAIL KHAIRAT - Abdul Jalil (Jurnal Dialog, 2015)
This study discusses the Social Capital of Dala’il Khairat actors at school Darul Falah school by Kiai Ahmad Bashir Kudus. This study aims to determine how donators’ social capital of Dala’il Khairat defined success in economic field. The donators are the alumni who live outside the pesantren and develop business ventures in some areas such as: Central Java, Yogyakarta, and Kuningan, West Java. By applying qualitative research this study was conducted in Pesantren Darul Falah Jekulo, Kudus, Central Java. Data were collected through participatory observation, interview, and documentation. The informants include mujiz Dala’il Khairat, school administrates, the students, community leaders, and alumni donators of Dala’il Khairat. It finds out that donators’ social capitals, such as the existence of social networks before and after donation, their business cooperation, and the trust, encouraged the pesantren economic success donators’ potential development. These social capitals have become a determining factor of developing commercialization among the donators who run their business and at the same time have helped the success in the economic field of the pesantren.